CRIF1 deficiency suppresses endothelial cell migration via upregulation of RhoGDI2. - Harsha Nagar (Public Library of Science (PLoS), 2021)
Rho GDP-dissociation inhibitor (RhoGDI), a downregulator of Rho family GTPases, prevents nucleotide exchange and membrane association. It is responsible for the activation of Rho GTPases, which regulate a variety of cellular processes, such as migration. Although RhoGDI2 has been identified as a tumor suppressor gene involved in cellular migration and invasion, little is known about its role in vascular endothelial cell (EC) migration. CR6-interacting factor 1 (CRIF1) is a CR6/GADD45-interacting protein with important mitochondrial functions and regulation of cell growth. We examined the expression of RhoGDI2 in CRIF1-deficient human umbilical vein endothelial cells (HUVECs) and its role in cell migration. Expression of RhoGDI2 was found to be considerably higher in CRIF1-deficient HUVECs along with suppression of cell migration. Moreover, the phosphorylation levels of Akt and CREB were decreased in CRIF1-silenced cells. The Akt-CREB signaling pathway was implicated in the changes in endothelial cell migration caused by CRIF1 downregulation. In addition to RhoGDI2, we identified another factor that promotes migration and invasion of ECs. Adrenomedullin2 (ADM2) is an autocrine/paracrine factor that regulates vascular tone and other vascular functions. Endogenous ADM2 levels were elevated in CRIF1-silenced HUVECs with no effect on cell migration. However, siRNA-mediated depletion of RhoGDI2 or exogenous ADM2 administration significantly restored cell migration via the Akt-CREB signaling pathway. In conclusion, RhoGDI2 and ADM2 play important roles in the migration of CRIF1-deficient endothelial cells.